PERJUANGAN POLITIK PEREMPUAN MERAIH KURSI DEWAN PERWAKILAN RAKYAT DAERAH DI KABUPATEN INDRAGIRI HILIR PADA PERIODE 2014-2019” - ", Fahri; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The public concern in political issues recently rises up. They concern to the embodiment of woman representation in Indonesian election. Hence, the power of woman attraction indeed takes another enthusiastic in some political issues. R.A Kartini ,Former political woman, drags the spirit in early her movement. The spirit of Kartini brings another chance for women empowered to be involved in political part. 30% of women quota proves their dedication for Kartini’s spirit. With constitution agreement, the public incredulity and hesitance still continue. The public assumption of women nature in line with their inabilities in politics is implicit. Moreover, women do not have a principal standing in political parties and appropriate rank in election process actually.Though, cultures, families, elites do not prevent their political willing for women interest needs. They build their own power through women organizations, background and hierarchy to compete in election process. The coherence both politic and women unified. Thus, because women consciousness of political rights. Affirmative action pushes women representation as constitution shows No. 8 2012 General Election of DPR, DPD dan DPD Chapter 56 Ayat (2), Dalam setiap 3 (tiga) bakal calon perempuan dapat ditempatkan pada urutan 1, atau 2, atau 3 dan demikian seterusnya, tidak hanya pada nomor urut 3, 6, dan seterusnya. Keyword : Woman and Politic, Affirmative Action, Election